First results from divertor operation in Wendelstein 7-X. (27th November 2018) - Pedersen, Thomas Sunn; König, Ralf; Krychowiak, Maciej; Jakubowski, Marcin; Baldzuhn, Jürgen; Bozhenkov, Sergey; Fuchert, Golo; Langenberg, Andreas; Niemann, Holger; Zhang, Daihong; Rahbarnia, Kian; Bosch, Hans-Stephan; et al.
Abstract: Wendelstein 7-X is a highly optimized stellarator that went into operation in 2015. With a 30 cubic meter volume, a superconducting coil system operating at 2.5 T, and steady-state heating capability of eventually up to 10 MW, it was built to demonstrate the benefits of optimized stellarators at parameters approaching those of a fusion power plant. We report here on the first results with the test divertor installed, during the second operation phase, which was performed in the second half of 2017. Operation with a divertor, and the addition of several new fueling systems, allowed higher density operation in hydrogen as well as helium. The effects that higher density operation had on both divertor operation and global confinement will be described. In particular, at high densities detachment was observed, and the highest fusion triple product for a stellarator was achieved.